(untitled) (Experimental biology, 2022)
The article talks about a large number of unused resources in the field of medicine, where endocrine- enzyme and special raw materials of farm animals can be used for medicinal purposes, an analysis of technologies for processing bile of cattle is carried out. The fact that the bile of wild animals contains a wide range of biologically active substances has been known since ancient times. The development of pharmacology makes it possible to fully reveal all the beneficial properties of endocrine-enzyme and special raw materials for the development of various therapeutic drugs. The demand for cattle on the world market is very high. Therefore, one of the effective directions is the collection and processing of endocrine-enzyme and special raw materials for the production of medical and veterinary drugs. Currently, endocrine-enzyme and special raw materials are not processed in Kazakhstan. Therefore, this article discusses the main directions in the field of bile processing and processing of meat obtained during slaughter of cattle, ways to develop technologies for long-term preservation of product quality indicators that improve its quality. The most effective way of long-term storage is canning, i.e. the process of thickening. Depending on the age and sex of the animal, the bile can be thick or liquid. Therefore, the thickening process took place within 12-15 hours. Depending on this result, the optimal parameters of the thickening process were determined. In the course of the study, the physical, chemical and biological composition, microbiological pa- rameters of bile were determined, and storage periods were established. The article presents the results of the study of bile.